Effects of thoracic spine mobilization on chest expansion in patients with chronic mechanical neck pain: a randomized controlled trial - Hanaa Ali Hafez; Mohamed Ahmed Mohamed; Ahmed Ibrahim Elarian; Mennaallahy Nasreldien; Asmaa Hossam; Osama yassin Abbas; Dina S Abd Allah (IP Iermakov S.S., 2024)
Background and Study Aim. Chronic mechanical neck pain significantly impacts the quality of life and functional capacity of individuals, often necessitating long-term management strategies. Traditional stretching exercises are commonly prescribed, but their effectiveness compared to other interventions remains underexplored. The objective of this study was to compare the effectiveness of traditional stretching exercise regimens against thoracic spine and rib mobilization in patients with chronic mechanical neck pain. Material and Methods. This randomized controlled trial included 30 patients aged between thirty and fifty years, all suffering from mechanical neck pain. Patients were randomly assigned to one of two groups, with 15 in each group (Group A: n=15; Group B: n=15). Group A received thoracic spine mobilization coupled with standard passive stretching exercises, whereas Group B underwent a traditional stretching exercise regimen. Both groups were evaluated using the visual analogy scale for pain, active cervical range of motion (ROM), and chest expansion, both before and after a two-week therapy course. Results. Findings from this study were analyzed using a two-way mixed-model multivariate analysis of variance (MANOVA). The results showed no significant differences between Group A (thoracic spine mobilization and standard passive stretching) and Group B (traditional stretching regimen) regarding pain intensity, active cervical range of motion, and chest expansion after the two-week intervention period (p > 0.05). However, significant improvements were observed within each group across all measured outcomes, including reductions in pain intensity and increases in cervical range of motion and chest expansion (p < 0.001). Conclusions. The study confirms that both passive stretching exercises and thoracic spine mobilization are beneficial interventions for enhancing physical outcomes in patients with mechanical nonspecific neck pain. These approaches are equally effective in improving overall physical functionality, underscoring their value in therapeutic settings for neck pain management.